Prevalence of alcohol intake and illegal drugs among the students at english medium private schools of Tripura, India (North Eastern States of India) - Biplab Jamatia (Wolters Kluwer Medknow Publications, 2022)
Background: Early initiation of alcohol use among adolescents can provide a useful indication of the potential future burden among adults including increased risk for academic failure, mental health problems, antisocial behavior, physical illness, risky sexual behavior, sexually transmitted diseases, early onset dementia, and the development of alcohol use disorders. The objective of this study is to measure the prevalence of alcohol consumption and illegal drug use among adolescent students studying in class ninth to eleventh standard in English medium private schools in Tripura, India. Methods: A cross sectional descriptive study was carried out in faith based English medium private schools of two selected subdivisions of Tripura, India. Students of class ninth to eleventh standard were selected for this current study. A validated questionnaire was used to find out the prevalence of alcohol and illegal drug intake. Results: A total of 565 (boys = 308, girls = 257) students participated in this study from four schools. The prevalence of alcohol intake (ever) among adolescent students was 28.2% [95% confidence interval (CI) 24.6-32.1]. The adolescent students of 1.7% (95% CI 0.9-3.1) consumed alcohol once a week in the past 6 months. It was observed that 4.2% (95% CI 2.8-6.3) of adolescents use illegal drugs. The study participants of 12.7% (95% CI 10.2-15.8) reported having close friends who were using illegal drugs. Conclusions: Significant percentages of adolescent students were involved in alcohol intake (ever) and use of illegal drugs.